Account ownership and use of financial services among individuals: Evidence from selected Sub-Saharan African economies. Issue 1 (13th March 2017) - Wale, Letenah Ejigu; Makina, Daniel
Abstract : Purpose: The purpose of this paper is to understand the effect of individual characteristics (such as sex, age, education and income) on the likelihood of account ownership and use in selected Sub-Saharan African (SSA) economies. Account use is operationalized into two constructs namely the use of account to save and the frequency of account use. Design/methodology/approach: Data from 18, 000 individuals from 18 SSA economies are used for the analysis. These data are sourced from the World Bank's Global Findex database. Simple probit and selection models are employed as econometric tools. Findings: Account ownership and use is found to be higher among males, middle aged, high income and educated individuals. The marginal effect of income and education is most pronounced suggesting more policy attention is required in respect of the two factors. Practical implications: Due to causality issues between financial inclusion and income, addressing the plight of the poor in financial inclusion projects will be a continuing challenge for policy makers. Originality/value: It supplements the dearth of econometric studies conducted on the topic. Furthermore, regional specific factors affect the generality of results which calls for such type of studies.